Internet connectivity disruption in Ghana (Ghana) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Ghana. Data sourced from IODA.
Network Disruption Incident ID: GH-2026-0053. Severity: critical. Confidence: 67%